1998
DOI: 10.1038/sj.onc.1201911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the zebrafish PEA3 ETS-domain transcription factor

Abstract: The PEA3 subfamily of ETS-domain proteins play important roles in regulating transcriptional activation and have been implicated in several tumorigenic processes. Here we describe the identi®cation of a further member of this family from zebra®sh which most likely represents a homologue of PEA3. A high degree of sequence conservation is observed in the ETS DNAbinding domain and acidic transcriptional activation domain. The DNA binding speci®city of zebra®sh PEA3 is virtually identical to that exhibited by mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
(50 reference statements)
2
45
0
Order By: Relevance
“…In comparison to Elk-1 and SAP-1, the relative binding e ciencies of zTCF-1 closely mirrors those exhibited by Elk-1 (Figure 4b). SAP-1 exhibits a lower siteselectivity and binds all the tested sites better than either zTCF-1 or Elk-1 (Figure 4b; Brown et al, 1998a). The DNA binding speci®city of zTCF-1 is therefore most similar to that of human Elk-1 (see Discussion).…”
Section: Dna Binding Properties Of Ztcf-1mentioning
confidence: 85%
See 2 more Smart Citations
“…In comparison to Elk-1 and SAP-1, the relative binding e ciencies of zTCF-1 closely mirrors those exhibited by Elk-1 (Figure 4b). SAP-1 exhibits a lower siteselectivity and binds all the tested sites better than either zTCF-1 or Elk-1 (Figure 4b; Brown et al, 1998a). The DNA binding speci®city of zTCF-1 is therefore most similar to that of human Elk-1 (see Discussion).…”
Section: Dna Binding Properties Of Ztcf-1mentioning
confidence: 85%
“…Autonomous binding is mediated by the ETS-domain alone and the binding speci®city of zTCF-1 closely resembles that of Elk-1 which exhibits a more stringent binding speci®city than either SAP-1 or SAP-2 (Figure 4, Shore et al, 1996;Brown et al, 1998a). It was previously demonstrated that the presence of amino acid D69 in the Elk-1 ETS-domain (V68 in SAP-1) is mainly responsible for generating this stringent binding speci®city (Shore et al, 1996).…”
Section: Dna Binding Properties Of Ztcf-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of scyba, which codes for a CXC-type chemokine, is also strongly expressed in the otic placodes from 12 hpf (Long et al, 2000). Transcripts for the ETS-domain transcription factors erm and pea3, and the FGF antagonist sprouty4, mark the otic placodes from early stages and appear to be direct transcriptional targets of FGF-mediated induction (Brown et al, 1998;Mü nchberg et al, 1999;Fü rthauer et al, 2001;Raible and Brand, 2001;Roehl and Nü sslein-Volhard, 2001; see the Role of FGF Signaling section). Expression of these genes overlaps with that of pax2.1 (Raible and Brand, 2001).…”
Section: Placode Inductionmentioning
confidence: 99%
“…To compare the two isoforms further we also performed co-transfection experiments in rabbit kidney RK13 cells in the presence of a luciferase reporter gene driven by the three times E74 Ets motifs. Taking into account the fact that transcriptional activation by PEA3 group members is enhanced by the PKA signaling pathway Brown et al, 1998), the involvement of this pathway in regulating transcripis represented by the large box, which contains the acidic (hatched box) and the ETS (black box) domains; the¯anking 5'-and 3'-untranslated regions are shown as small boxes. The acidic and the ETS domains are each composed of three di erent exons.…”
Section: Comparison Of the Binding And Transcriptional Capacities Of mentioning
confidence: 99%